Evaluation of Maturity Level of E-Procurement Application Systems - Sandy Kosasi; I Dewa Ayu Eka Yuliani; Vedyanto Vedyanto (Proceeding of the Electrical Engineering Computer Science and Informatics, 2015)
The availability of service levels and informationtechnology governance supports immensely influences theperformance and competitiveness of the companies. The value ofthe maturity level of the information technology governance isgoing to affect the simplicity and the smoothness of punctuallyobtaining relevant and accurate information in the process ofmanagerial decision making. This research aims to cognise thematurity level and provides recommendations of the model ofinformation technology governance, particularly the electronicapplication system of procurement at DS (Deliver and Support)Domain through the use of COBIT 4.1 Framework. The result ofthis research reflects that the lowest value of maturity level goesto DS4 (Ensure Continuous Service) Process, i.e. 1.750. Theinformation technology governance of DS4 possesses theconnection between the control objective inputs comprising PO2,PO9, AI2, AI4, and DS1, and the control objective outputsconsisting of PO9, DS1, DS8, DS9, DS11, and ME1. To be moreeffective in reaching the third maturity level (i.e. defined process)with the rounding index of 2.50, processes linked to DS4 arerequired to build a relationship with the third party as theinformation service provider with a fine quality, to monitor theservice delivery through verification, and to ensure sustainableconformity and compliance.